Higher-order space charge field effects on the self-deflection of bright screening spatial solitons in two-photon photorefractive crystals - Jiang, Qichang; Su, Yanli; Ji, Xuanmang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We investigate the effects of higher-order space charge field on the self-deflection of bright screening spatial solitons due to two-photon photorefractive effects by a numerical method under steady-state conditions. The expression for an induced space charge electric field including higher-order space charge field terms is obtained. Numerical results indicate that bright screening solitons undergo self-deflection process during propagation, and the solitons always bend in the opposite direction of the c axis of the crystal. The self-deflection of bright screening solitons can experience considerable increase especially in the regime of high bias field strengths. Relevant examples are provided.
Optica Applicata, Vol. 40, 2010, nr 2, s. 481-490
Keywords: optyka; non-linear optics; two-photon photorefractive effect; bright screening spatial solitons; self-deflection